Renovation of Public Lighting Systems in Cultural Landscapes: Lighting and Energy Performance and Their Impact on Nightscapes - Lodovica Valetti; Francesca Floris; Anna Pellegrino (Energies, 2021)
The technological innovation in the field of lighting and the need to reduce energy consumption connected to public lighting are leading many municipalities to undertake the renewal of public lighting systems, by replacing the existing luminaires with LED technologies. This renovation process is usually aimed at increasing energy efficiency and reducing maintenance costs, whist improving the lighting performance. To achieve these results, the new luminaires are often characterised by a luminous flux distribution much more downward oriented, which may remarkably influence and alter the perception of the night image of the sites. In this study the implications of the renovation of public lighting systems in terms of lighting and energy performance as well as the effects relating to the alteration of the night image, in historical contexts characterized by significant landscape value, are analysed. Results, along with demonstrating the positive effect that more sustainable and energy efficient lighting systems may have on the lighting performance and energy consumptions of public lighting systems, evidences the impact they may have on the alteration of the nocturnal image.